From nation-state to market: The transformations of religion in the global era, as illustrated by Islam. Issue 3 (3rd July 2018) - Gauthier, François
ABSTRACT: This article has three parts. The first analyses how notions of the market and of marketisation have been literally and metaphorically applied to the study of religion. The article argues in favour of thinking consumption as the circulation and exchange of symbols rather than goods, and therefore reintegrates economic phenomena into the fold of history and socio-anthropology. The second part argues that the major transformations of the last half-century are best understood as the shift from a national-statist religious regime to a market regime cast against the backdrop of globalisation. The rise of consumerism as a social and cultural ethos, the spread of neoliberal and managerial ideologies, are the key processes which underlie a major reconfiguration of societies and cultures on a global scale. The third part argues that the important mutations occurring within Islam – as illustrated by Indonesian Islam – demonstrates the heuristic potential of the suggested approach.